The OntoREA Accounting Model: Ontology-based Modeling of the Accounting Domain - Fischer-Pauzenberger, Christian; Schwaiger, Walter (Complex Systems Informatics and Modeling Quarterly, 2017)
McCarthy developed a framework for modeling the economic rationale of different business transactions along the enterprise value chain described in his seminal article “The REA Accounting Model – A Generalized Framework for Accounting Systems in a Shared Data Environment” Originally, the REA accounting model was specified in the entity-relationship (ER) language. Later on other languages – especially in form of generic data models and UML class models (UML language) – were used. Recently, the OntoUML language was developed by Guizzardi and used by Gailly et al. for a metaphysical reengineering of the REA enterprise ontology. Although the REA accounting model originally addressed the accounting domain, it most successfuly is applied as a reference framework for the conceptual modeling of enterprise systems. The primary research objective of this article is to anchor the REA-based models more deeply in the accounting domain. In order to achieve this objective, essential primitives of the REA model are identified and conceptualized in the OntoUML language within the Asset Liability Equity (ALE) context of the traditional ALE accounting domain.